Dopamine D(1) receptor-mediated inhibition of NADPH oxidase activity in human kidney cells occurs via protein kinase A-protein kinase C cross-talk - Yu, Peiying (2010)
Dopamine cellular signaling, via the D(1) receptor (D(1)R), involves both protein kinase A (PKA) and protein kinase C (PKC), but the PKC isoform involved has not been determined. Therefore, we tested the hypothesis that the D(1)R-mediated inhibition of NADPH oxidase activity involves cross-talk between PKA and specific PKC isoform(s). In HEK-293 cells heterologously expressing human D(1)R (HEK-hD(1)), fenoldopam, a D(1)R agonist, and phorbol-12-myristate-13-acetate (PMA), a PKC activator, inhibited oxidase activity in a time- and concentration-dependent manner. The D(1)R-mediated inhibition of oxidase activity (68.1±3.6%) was attenuated by two different PKA inhibitors, H89 (10 µmol/L) (88±8.1%) and Rp-cAMP (10 µmol/L) (97.7±6.7%), and two different PKC inhibitors, bisindolylmaleimide I (1 µmol/L) (94±6%) and staurosporine (10 nmol/L) (93±8%), which by themselves, had no effect (n=4–8/group). The inhibitory effect of PMA (1 µmol/L) on oxidase activity (73±3.2%) was blocked by H89 (100±7.8%) (n=5–6/group). The PMA-mediated inhibition of NADPH oxidase activity was accompanied by an increase in PKCθ(S676), an effect that was also blocked by H89. Fenoldopam (1 µmol/L) also increased PKCθ(S676) in HEK-hD(1) and human renal proximal tubule (RPT) cells. Knockdown of PKCθ with siRNA in RPT cells prevented the inhibitory effect of fenoldopam on NADPH oxidase activity. Our studies demonstrate for the first time that cross-talk between PKA and PKCθ plays an important role in the D(1)R-mediated negative regulation of NADPH oxidase activity in human kidney cells.